POLA TUBERKULOSIS PADA RONTGEN DADA SEORANG PEREMPUAN BERUSIA 16 TAHUN DENGAN PNEUMONIA ASPIRASI TERKAIT TENGGELAM DI NEGARA ENDEMIS, INDONESIA: LAPORAN KASUS - Athoillah, Nabil; Tias, Ditya Pramudyaning; Fardhani, Ichlasul Mahdi; Kurniawan, Setiadi Drajad (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2025)
Background: Aspiration pneumonia is a process of lung infection that occurs after abnormal fluid ingress in the lower respiratory tract. Drowning is one of the most common cause of aspiration pneumonia. The diagnosis of aspiration pneumonia can be confirmed through history taking, physical examination, and supporting examination for appropriate therapy. Here we report a case of aspiration pneumonia due to drowning that had a radiological appearance of fibroinfiltrates resembling pulmonary TB. Case Illustration: A 16-year-old girl presented with symptoms of decreased consciousness, fever, shortness of breath, and haemoptysis after drowning in a river. The patient was diagnosed with aspiration pneumonia based on clinical manifestations, but the patient was suspected of having pulmonary TB from the chest X-ray. The patient was treated according to the management of aspiration pneumonia rather than TB to avoid treatment resistance and side effects. Conclusion: This report shows the importance to assess the symptoms of aspiration pneumonia or TB in children with symptoms of shortness of breath and haemoptysis to avoid inappropriate therapy.